Peran Pimpinan Pesantren Dalam Mengelola Program Tahfizul Qur’an Di Pesantren El-Madinah Wahdah Islamiyah Bone Bolango - Ronal Gani; Muh. Hasbi; Syahrial Labaso (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to determine the strategic role of the Islamic boarding school leader in managing the Tahfizul Qur'an Program at Pesantren El-Madinah Wahdah Islamiyah Bone Bolango, covering the management functions of planning, organizing, actuating, controlling, and evaluating, as well as the supporting and inhibiting factors. This research employed a qualitative approach with a case study design. Data collection techniques included structured interviews, field observations, and documentation analysis. The results showed that planning is conducted through collective deliberation with tahfiz teachers to determine realistic targets and schedules. Organizing involves clear division of labor based on student grade levels to optimize supervision. Actuating is implemented systematically by clustering students' initial reading abilities and providing an intensive 3-month Dirosa method for preparation. Controlling incorporates regular morning field visits and tracking sheets. Evaluating consists of weekly and monthly coordination meetings as well as end-of-semester Tasmi' examinations. Supporting factors include teacher discipline, student motivation, and a digital reporting system via a website. Meanwhile, inhibiting factors consist of students' mental fatigue, limited human resources, and tightly packed institutional schedules.